Penerapan Integrated Marketing Communication (IMC) melalui Media Sosial Instagram dalam Meningkatkan Brand Awareness pada UMKM Fortune Pao di Kota Batam - Hasan, Golan; Gilbert, Kerdion; Celline; Jolyn; Calvin (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
This study aims to analyze the implementation of Integrated Marketing Communication (IMC) strategies through the social media platform Instagram to enhance brand awareness of the MSME (Micro, Small, and Medium Enterprise) Fortune Pao in Batam City. Employing a qualitative descriptive approach, data were collected through direct observation of digital marketing activities and content analysis on Fortune Pao's Instagram account. The findings indicate that Integrated Marketing Communication (IMC) implementation, encompassing media integration, message consistency, and two-way communication, effectively strengthens brand awareness by fostering intensive consumer interaction and delivering a uniform message. The study recommends enhancing promotion effectiveness evaluation and strengthening cross-media coordination to maximize Integrated Marketing Communication (IMC) outcomes. These results offer valuable insights for MSME practitioners aiming to optimize digital marketing strategies to expand market reach and competitiveness in the digital era.